2022
DOI: 10.54337/ojs.td.v29i1.7439
|View full text |Cite
|
Sign up to set email alerts
|

Revision af Transportøkonomiske Enhedspriser 2022

Abstract: De Transportøkonomiske Enhedspriser har sammen med modellen TERESA i mange år udgjort Transportministeriets grundlag for samfundsøkonomiske analyser inden for transportsektoren i Danmark.I 2022 er enhedspriserne blevet revideret på to områder, som har relation til den grønne omstilling: grønne køretøjer og emissioner. Desuden er mulighederne for følsomhedsanalyser af klimaomkostningerne blevet udvidet.Blandt de vigtigste fornyelser kan nævnes, at der i kørselsomkostningerne nu tages højde for, at afgifterne på… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A Danish study found that the number of trip legs, the drive time, and the requirement to charge the vehicle all had negative effects on the probability of choosing an EV. On the other hand, precipitation and urban areas had positive effects on the probability of choosing an EV [14]. A study in Switzerland modeled household vehicle choice as a function of trip attributes, socio-demographic variables, and spatiotemporal variables [13].…”
Section: Usagementioning
confidence: 99%
See 2 more Smart Citations
“…A Danish study found that the number of trip legs, the drive time, and the requirement to charge the vehicle all had negative effects on the probability of choosing an EV. On the other hand, precipitation and urban areas had positive effects on the probability of choosing an EV [14]. A study in Switzerland modeled household vehicle choice as a function of trip attributes, socio-demographic variables, and spatiotemporal variables [13].…”
Section: Usagementioning
confidence: 99%
“…Since this study intends to identify the types of trips that are most likely to be made by EVs in multi-vehicle households, individual trip attributes (e.g., trip purpose, trip distance, and number of passengers) were considered in the modeling framework. Trip attributes have been previously used in studies that modeled EV usage [13,14]. Based on these studies, a number of trip attributes were considered to be included in the model.…”
Section: Variable Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example, Denmark has implemented LEZs specifically for HDDTs since 2008. According to one study, the LEZ in Copenhagen was associated with a 5% reduction in average PM2.5 concentrations ( 15 ). However, it should be noted that the evaluation of the efficacy of LEZs based on air quality measurement data is complex as there are other confounding factors (e.g., variation in meteorological conditions, fleet turnover) that could affect the levels of air pollutant concentration in the LEZs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…22 Today prominent mobilities scholars such as Ole B. Jensen use science and technology studies and post-humanist philosophy to discuss the development of human-technology futures. 23 Others may draw on migration and tourism theory to explore how human communities and environments may survive environmental 24 and organizational crises 25 in the Anthropocene. Studies of travel mobilities as pedagogy 26 or aspects of professional and leisure rhythms 27 sit next to atmospheric interrogations of technology, tourism 28 and artistic 29 publics, and work-related automobility routines 30 to frame mundane but central to the production of sociality "events" and situations.…”
Section: Space Place and Community-makingmentioning
confidence: 99%